POLA KOMUNIKASI INTERPERSONAL GURU DAN ANAK DALAM PEMBELAJARAN PHONICS DI BRIGHT CUBS LEARNING CENTER - Rachmad, Teguh Hidayatul; Octaviana , Stefani; Subandi, Zera Edenzwo (LPPM Stikosa - AWS, 2025)
This study aims to describe the patterns of interpersonal communication in phonics learning for early childhood at Bright Cubs Learning Center. A descriptive qualitative approach was employed, using in-depth interviews with three phonics teachers and two parents. This research applies Social Learning Theory and Symbolic Interactionism to explain how communication between teachers and students shapes learning experiences and children’s perceptions of letters and sounds. The findings reveal that warm, responsive, and interactive communication patterns play a crucial role in building children's self-confidence and facilitating their understanding of phonics. Symbolic communication expressed through facial expressions, body movements, and vocal intonation provides meaningful learning cues for children in learning to read. The interaction fosters not only early literacy skills but also the broader development of children's interpersonal communication. These findings highlight the importance of the quality of interpersonal relationships in early childhood education, particularly in the phonics learning context.